Overcoming Intellectual Unemployment through Entrepreneurship Learning Transformation: A Case Study on Sharia Economic Law Study Program of Unismuh Makassar - Fakhruddin Mansyur; Jasri Jasri; Mowafg Masuwd (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
The number of job vacancies in Indonesia is still far less than the number of job seekers every year. This shows the inability of both the government and companies to create job opportunities for generation Z in Indonesia and at the same time emphasizes that educational institutions are not able to create an easy generation that is careful about entrepreneurship, even though the level of young entrepreneurs is one of the benchmarks of a developed country. The aim of this research is to find a formula for increasing the entrepreneurial spirit of Generation Z through effective entrepreneurship learning. The type of research used is field research with a quantitative approach. The object of this research is students and graduates of the Unismuh Makassar Sharia Economic Law Study Program. The results of this study indicate that of the two variables studied, namely human resources in this case are lecturers (X1) and entrepreneurship learning (X2) it is known that the variable X1 does not influence the growth of student entrepreneurial spirit while entrepreneurship learning has a positive and significant effect on growth. student entrepreneurial spirit. So, it can be concluded that to build and foster the entrepreneurial spirit of students there needs to be improvement and great attention to the entrepreneurship learning process which is capable of being a means of creating Generation Z who are fond of entrepreneurship.